Penataan Lahan Pekarangan Untuk Mendukung Budidaya Lebah Madu di Desa Gelangsar, Kabupaten Lombok Barat - Arben Virgota; Suripto; A. Jupri; Rina Kurnianingsih; Nur Indah Julisaniah; Baiq Farista (Universitas Mataram, 2021)
The resident's yard of Gelangsar Village generally has not been used optimally. In some parts of the yard are overgrown with shrubs whose benefits are not yet known. This program aims to introduce yard management methods that can provide economic benefits, namely the innovation of flowering plant gardens to support honey bee cultivation. The method used in this program is socialization and the formation of a pilot project. The socialization focused on introducing the arrangement of the yard with flowering plants. The pilot project was made on the land of one of the partner residents. In this pilot project, innovations in planting flowering plants with vertical garden and honey bee cultivation methods are applied. Through this pilot method, it is hoped that the people of Gelangsar Village can apply the innovations offered independently. This program has been successfully implemented. Partner residents are willing to apply the innovation of a combination of flowering plant gardens and honey bee cultivation.